Undernutrition and associated common comorbidities among 6 -59 months old children - Rehan, Abu; Kishore, Surekha; Singh, Mahendra; Bahurupi, Yogesh; Aggarwal, Pradeep; Jain, Bhavna (Indian Journal of Community Health, 2020)
Background: Undernutrition has long been a major public health concern in developing country like India as a leading cause of child morbidity and mortality. Aim & Objectives: To assess undernutrition in under five children and various associated factors affecting it. Methods and Material: A community based cross sectional study was conducted among 400 under five children in Rishikesh. Results: The prevalence of underweight was 37.3%, stunting was 43.3% and wasting was 24.5% respectively. Common morbidity emerged as significant predictors of under nutrition. Conclusion: The burden of common morbidities and prevalence of malnutrition among under-five children in this community is very high.